Regulation of S-Adenosylmethionine Synthetase in Escherichia coli - Holloway, Caroline T. (1970)
Addition of methionine to the growth medium of Escherichia coli K-12 leads to a reduction in the specific activity of S-adenosylmethionine (SAM) synthetase. Thus the enzyme appears to be repressible rather than inducible. Mutant strains (probably metJ(−)) are constitutive for SAM synthetase as well as for the methionine biosynthetic enzymes, suggesting that the regulatory systems for these enzymes have at least some elements in common. Cells grown to stationary phase in complete medium, which have low specific activities of the enzymes, were routinely used for derepression experiments. The lag in growth and derepression when these cells are incubated in minimal medium is shortened by threonine. Ethionine, norleucine, and α-methylmethionine are poor substrates or nonsubstrates for SAM synthetase and are ineffective repressors. Selenomethionine, a better substrate for SAM synthetase than methionine, is also slightly more effective at repression than methionine. Although SAM is considered to be a likely candidate for the corepressor in the control of the methionine biosynthetic enzymes, addition of SAM to the growth medium does not cause repression. Measurement of SAM uptake shows that too little is taken into the cells to have a significant effect, even if it were active in the control system.